Guarda Nacional Republicana Risk Analysis and Revenue Management System. Case Study: Comando Territorial de Lisboa - Neves, Andreia; Rosado, David Pascoal; Regueira, Diogo; Comba Lopes, Helga Santa; Borges, José (Journal of Reviews on Global Economics, 2020)
The complexity and decentralization of revenue along with the need for effective allocation of public resources in the Guarda Nacional Republicana are the core of this research. The present research aims to analyze the impacts of a risk management system in the decision-making process. In this context, the objective is to identify and analyze the most critical areas and control mechanisms implemented in the monitoring of the inherent risks in the process of road accident certificates. Thus, the purpose is to analyze the impacts of a risk management system in the process understudy in the Comando Territorial de Lisboa and, consequently, its consequences in the administration of the internal resources of the Guarda Nacional Republicana. The findings show that the most critical areas in the process of own revenue management are related to the collection and saving of public funds, therefore, the control mechanisms implemented reduce the margin of error. However, it is noted that the revenue is collected in a decentralized manner associated with various computer systems without interoperability which implies technical inconsistencies that severely affect their management. Thus, it is concluded that an adequate risk management methodology reveals an optimization of the application of the internal resources of the Guarda Nacional Republicana based on the alignment of the strategic objectives with the institution´s risk assessment. In conclusion, a risk management system is a tool meant to support decision making allied to the safeguarding of assets, the protection of the institutional image and the fulfillment of the mission.